Investigating External Causes for Lack of Reading Motivation among Private High School Students - Rohmah, Riza Mi’rotul; Imaniar, Fahmy (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
This article investigates the critical issue of dwindling reading motivation among high school students in Surabaya, Indonesia, specifically focusing on English texts. Against the global context of the paramount importance of reading proficiency, the data reveal a troubling decline in reading interest, particularly evident among private high school students in metropolitan areas. The study advocates for implementing the multiple intelligences strategy and emphasizes the crucial role of teachers in fostering motivation and interest in reading English texts. Using a descriptive qualitative approach with participants from a Surabaya-based private high school, the research employs convenience sampling, incorporating interviews and observations for data collection. The findings spotlight external factors contributing to students' diminished motivation, encompassing unappealing book covers, underutilized free time, comprehension challenges, and limited book availability. The ensuing discussion underscores the necessity for targeted interventions by educators and policymakers, extending beyond academic success to cultivate a positive reading culture. Such a culture contributes to holistic student development, nurturing cognitive abilities, effective communication skills, and instilling a lifelong love for learning. In conclusion, the study emphasizes the profound implications of investing in a positive reading culture for the personal and intellectual growth of high school students in Indonesia.